Determinants and impact of farmers' participation in social media groups: Evidence from irrigated areas of Kazakhstan and Uzbekistan - Abdusame Tadjiev; Zafar Kurbanov; Nodir Djanibekov; Ajit Govind; Akmal Akramkhanov (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2023)
The spread of information and communications technology (ICT) in Central Asia has reached a point where most farmers use smartphones with mobile internet access, providing an opportunity for a cost-effective and timely access to agricultural information and extension services. When extension service provision is poor and does not reflect farmers' immediate needs, farmers often seek other sources of information, such as exchanging knowledge with their peers via social media groups in instant messaging applications (apps). Using the findings of a farm-level survey conducted in 2022 in irrigated areas of Kazakhstan and Uzbekistan, we study behavior and attitudes of farmers in terms of participation in smartphone-based social media groups and its impact of farm performance. We find that in the two country contexts underlying reasons for participation in social groups differ. In Kazakhstan, participation decisions are made by those who have better access to a mobile internet connection, are younger, have agriculture-related education, have a wider communication circle on phone with more than four individuals, cultivate fewer crops, have lands with low soil quality and poor irrigation water access, as well as located in remote areas. In Uzbekistan participation decisions are made by those who see the relevance of mobile internet for their farm business, have own agronomic knowledge, are open to new things, care less about the opinion of other farmers, have higher perception about freedom in crop choice, have off-farm work, as well as poor irrigation water access. These findings suggest farmers' participation in agricultural information-sharing groups (AISG) is influenced less by the type of cultivated crops or farm size, but by their institutional environment. The findings are relevant for developing private strategies and public policies to spread digital technologies among Central Asia's farmers. When introducing smartphone-based digital advisory services policymakers are recommended to start scaling up with younger and more educated farmers who rely on their own knowledge and are more open to embracing new ways of farming and interaction. Farmers' decision-making autonomy will be crucial for converting digital transformation in agriculture into farm benefits.
urn:nbn:de:gbv:3:2-977351
Keywords: 330; Extension services; self-help groups; knowledge exchange; partcipation determinants; Central Asia